Ecclesiastical Acts of the Holy See: Their Classification and Juridical Weight - Rudinskas, Aurimas; Machovenko, Jevgenij (Teisė, 2024)
By identifying the functions that the Roman Catholic Church assigns to itself, categorizing ecclesiastical acts according to these functions, and examining the concept of the ecclesiastical power of governance, the authors of this article aims to provide some guidelines and rules that would enable both lay lawyers and Church hierarchs living and working in Lithuania to more correctly assess the juridical weight of the Holy See’s ecclesiastical acts which fall under the domain of Ecclesiastical Law (regulating the relationships of the faithful within the Church itself, and not with other international legal entities). The study shows that a significant number of acts of the Holy See cannot be equated with the concepts of ‘legal acts’ and ‘papal acts’, and their legal weight cannot be determined solely by the title of the act. A detailed content analysis is required.